Efektivitas Peran Chatgpt Sebagai Alat Bantu Penyelesaian Tugas Akademik Mahasiswa - Eka Finanti Simamora; Imel Simanungkalit; Prihatin Ningsih Sagala; Nurcahaya Br Zandroto; Putri Br Tarigan; Rival Ananda Gisty (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
This study aims to analyze the effectiveness of ChatGPT as a tool to help students complete academic assignments. Using a quantitative descriptive method, this study involved 150 6th semester students of the Mathematics Education Study Program selected through a simple random sampling technique. Data were collected through an online questionnaire that measured the intensity of ChatGPT use, ease of understanding the material, and its impact on learning outcomes. The results showed that the majority of students felt helped by the use of ChatGPT, especially in compiling essay assignments, understanding complex academic concepts, and increasing self-confidence in solving math problems. However, it was found that excessive use has the potential to reduce learning motivation if students rely too much on instant answers. Therefore, wise use of ChatGPT and integration with conventional learning methods is highly recommended so that students continue to develop critical thinking skills and independence in learning.